Implementation of Management Functions in Activities of Al-Fairus Mosque Pekalongan - Hanif Ardiansyah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
The mosque is the center of worship for Muslims. Problems that often occur in mosques such as inadequate facilities, the condition of infrastructure is still apprehensive, and the environment around the mosque is not taken care of. Even though the existence of the mosque at the time of Rasulullah SAW was not only used as a center of worship, but also had a role as a social center when the Prophet migrated to Medina. This is what the Al-Fairus Pekalongan Mosque has done, which positions the mosque as a center for community activities. This type of research is qualitative with a descriptive writing design in the context of the field or field research. Data collection techniques were obtained through interviews and observation, then the data were analyzed using the theory according to Miles and Huberman. The results of this study are that the application of management functions at the AL Fairus is in accordance with existing theories, starting from planning which includes the physical planning of the mosque and planning of mosque activities. Organizing activities which include the division of tasks in financial management, the construction of mosques, mosque shop houses, lodging and Hajj and Umrah unit, as well as mosque activities. Mobilization activities which include movement activities for the physical improvement of mosques as well as movements for increasing the functions of mosques. While Supervision activities are carried out through supervision of the physical activities of the mosque and the functions of the mosque. The impact of the Implementation of the Management Function on the Al-Fairus Pekalongan congregation is to reduce the community's unemployment rate, improve the congregation's economy, and the congregation gain useful knowledge that can be applied and applied in their daily activities.